Respostas
respondido por:
2
________________
DCD = √[(-2 - (-1)]² + (3 - 4)²
============================
______________
DCD = √( - 2 + 1)² + (-1)²
============================
_________
DCD = √ (-1)² + 1
=================
_____
DCD = √ 1 + 1
=================
__
DCD = √ 2
DCD = √[(-2 - (-1)]² + (3 - 4)²
============================
______________
DCD = √( - 2 + 1)² + (-1)²
============================
_________
DCD = √ (-1)² + 1
=================
_____
DCD = √ 1 + 1
=================
__
DCD = √ 2
respondido por:
1
d(C,D) = √
(Xa - Xb)² + (Ya - Yb)²
d(C,D) = √ [-1 - (-2)]² + (4 - 3)²
d(C,D) = √ (1 + 1)
d(C,D) = √ 2
d(C,D) = √ [-1 - (-2)]² + (4 - 3)²
d(C,D) = √ (1 + 1)
d(C,D) = √ 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás